APPLICATION OF NETWORK ANALYSIS CRASHING METHOD IN EVALUATING THE SCHEDULE OF NAVAL BASE FACILITY DEVELOPMENT PROJECT - Raditya Novianto; Suparno Suparno; Sutrisno Sutrisno; Abdul Rahman (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
A project of base facility is a kind of routine developing in Indonesian Naval. In this developmentt is necessary to develop methods in measuring performance and evaluating project time through a more accurate critical path feature. The research problem statement is how to evaluate the project schedule related to the time and cost of the Indonesian Navy's facility construction project by conducting a case study as a study for project scheduling at a later stage. The research objective is to identify the critical path of the project through network analysis, determine the factors that cause delays and how to overcome them, and calculate the time effectiveness and cost-efficiency of the project based on the calculation of scheduling acceleration. In this study, project performance measurement was carried out using the Earned Value Method (EVM) and network analysis using the Precedence Diagram Method (PDM). The solution to overcome delays with the crashing project method. The results of the discussion identified 15 critical path activities. The factor causing the delay is the delay in activities on the critical path due to the low level of productivity of the workforce group. The crashing method through additional 2 hours/day overtime can solve the problem of delays so that project implementation can be accelerated from the implementation of 256 working days to 226 working days (11.72% effectiveness) with the initial project cost of Rp. 74,316,727,585.00 reduced to Rp. 72,152,162,704.00 (2.91% efficiency). It will be measurable and reasonable in responsibility when it was suitable with the target. Keywords : Network Analysis, Naval Base, and Project Development.